The protective arm of the renin‐angiotensin system may counteract the intense inflammatory process in fetuses with posterior urethral valves - Natalia P. Rocha; Fernando M. Bastos; Érica L.M. Vieira; Thiago R.R. Prestes; Katia D. da Silveira; Mauro M. Teixeira; Ana Cristina Simões e Silva (Brazilian Society of Pediatrics, 2019)
Objective: Posterior urethral valve is the most common lower urinary tract obstruction in male children. A high percentage of patients with posterior urethral valve evolve to end‐stage renal disease. Previous studies showed that cytokines, chemokines, and components of the renin-angiotensin system contribute to the renal damage in obstructive uropathies. The authors recently found that urine samples from fetuses with posterior urethral valve have increased levels of inflammatory molecules. The aim of this study was to measure renin-angiotensin system molecules and to investigate their correlation with previously detected inflammatory markers in the same urine samples of fetuses with posterior urethral valve. Methods: Urine samples from 24 fetuses with posterior urethral valve were collected and compared to those from 22 healthy male newborns at the same gestational age (controls). Renin-angiotensin system components levels were measured by enzyme‐linked immunosorbent assay. Results: Fetuses with posterior urethral valve presented increased urinary levels of angiotensin (Ang) I, Ang‐(1‐7) and angiotensin‐converting enzyme 2 in comparison with controls. ACE levels were significantly reduced and Ang II levels were similar in fetuses with posterior urethral valve in comparison with controls. Conclusions: Increased urinary levels of angiotensin‐converting enzyme 2 and of Ang‐(1‐7) in fetuses with posterior urethral valve could represent a regulatory response to the intense inflammatory process triggered by posterior urethral valve. Resumo: Objetivo: A válvula de uretra posterior é a obstrução do trato urinário inferior mais comum em crianças do sexo masculino. Uma alta porcentagem de pacientes com válvula de uretra posterior evolui para doença renal em estágio final. Estudos anteriores mostraram que citocinas, quimiocinas e componentes do sistema renina‐angiotensina contribuem para o dano renal em uropatias obstrutivas. Recentemente, descobrimos que amostras de urina de fetos com válvula de uretra posterior tinham níveis aumentados de moléculas inflamatórias. O objetivo deste estudo foi medir as moléculas de renina‐angiotensina e investigar sua correlação com marcadores inflamatórios previamente detectados nas mesmas amostras de urina de fetos com válvula de uretra posterior. Métodos: Amostras de urina de 24 fetos com válvula de uretra posterior foram coletadas e comparadas com amostras de urina de 22 recém‐nascidos saudáveis de mesma idade gestacional (controles). Os níveis dos componentes de SRA foram medidos por ensaio de imunoabsorção enzimática. Resultados: Os fetos com válvula de uretra posterior apresentaram níveis urinários aumentados de angiotensina (Ang) I, Ang‐(1‐7) e enzima conversora de angiotensina 2 em comparação com os controles. Os níveis de enzima conversora de angiotensina eram significativamente menores e os níveis de Ang II eram semelhantes nos fetos com válvula de uretra posterior em comparação com os controles. Conclusões: O aumento dos níveis urinários de enzima conversora de angiotensina 2 e de Ang‐(1‐7) em fetos com válvula de uretra posterior poderia representar uma resposta regulatória ao intenso processo inflamatório desencadeado pela válvula de uretra posterior. Keywords: Posterior urethral valve, Renin-angiotensin system, Angiotensin II, Angiotensin‐(1‐7), ACE2, Inflammation, Palavras‐chave: Válvula de uretra posterior, Sistema renina‐angiotensina, Angiotensina II, Angiotensina‐(1‐7), ACE2, Inflamação